The Tamyiz Method, Motto Internalization, and Students' Learning Character in Kitab Kuning Learning - Hadi Suhandi Saja; Momod Abdul Somad; Mupid Hidayat (Journal of General Education and Humanities, 2026)
Kitab kuning learning in pesantren requires mastery of Nahwu and Shorof while fostering students' cognitive, affective, and value-based learning character. Previous studies have mainly emphasized cognitive outcomes, with limited evidence explaining how instructional methods contribute to character development through value internalization. This study examined the effectiveness of the Tamyiz Method and the mediating role of the Tamyiz motto. A mixed-methods sequential explanatory design was employed involving 60 junior secondary students at Bayt Tamyiz Islamic Boarding School, divided into experimental and control groups. Data were collected using a kitab kuning comprehension test, questionnaires, observations, and interviews, and analyzed using t-tests, MANOVA, mediation analysis, and thematic analysis. The experimental group showed higher improvement in kitab kuning comprehension (N-Gain = 0.72), with very large effect sizes for comprehension (d = 2.41), learning mentality and enthusiasm (d = 2.68), and motto internalization (d = 3.21). Motto internalization partially mediated the relationship between the Tamyiz Method and learning character (indirect effect = 1.12; proportion mediated = 72.7%). These findings indicate that integrating instructional innovation with value internalization can strengthen learning outcomes and character development in pesantren.